2022
DOI: 10.26480/egnes.01.2022.19.31
|View full text |Cite
|
Sign up to set email alerts
|

Value Chain Analysis of Potato in Tokha Municipality of Kathmandu District, Nepal

Abstract: The study was carried out in Tokha Municipality of Kathmandu district from April, 2020 to June, 2020 to map the value chain of potatoes and assess the productivity and profitability within the existing value chain. Altogether 50 potato producers were selected along with 5 aggregators, 5 wholesalers, 5 retailers and 10 consumers using the random purposive sampling technique. The primary data were collected through field survey, focus group discussion and key informant interviews and secondary data were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…In the study area, wholesalers and retailers played the part of processors. This is different from the finding of Tokha municipality (Shrestha et al, 2022), where they were identified as separate actors in the value chain. The major enablers or supporting actors were the Agriculture Knowledge Centre (AKC), Project Implementation Unit (PIU), Potato Zone, District Agriculture Development Office (DADO), NGOs (Sahara Nepal), INGOs, JTAs, Agriculture and Extension officers, Agricultural Development Bank Ltd. (ADBL), and microfinance.…”
Section: Functionscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the study area, wholesalers and retailers played the part of processors. This is different from the finding of Tokha municipality (Shrestha et al, 2022), where they were identified as separate actors in the value chain. The major enablers or supporting actors were the Agriculture Knowledge Centre (AKC), Project Implementation Unit (PIU), Potato Zone, District Agriculture Development Office (DADO), NGOs (Sahara Nepal), INGOs, JTAs, Agriculture and Extension officers, Agricultural Development Bank Ltd. (ADBL), and microfinance.…”
Section: Functionscontrasting
confidence: 99%
“…5030 per quintal. Therefore, the producer's share in consumer's rupee is only 51.68% which is significantly lower than the producer's share of 72.43% in Tokha municipality, Kathmandu (Shrestha et al, 2022). The finding showcases that the producer's share is not satisfactory because intermediaries are getting almost half of the share from the consumer's pay.…”
Section: Producer's Share and Price Spreadmentioning
confidence: 83%
See 1 more Smart Citation
“…cost of NRs 11,244.11 per kattha, or around NRs 244,882.2 per hectare in Potato cultivation which is similar to previous findings by(Sapkota et al, 2019;Shrestha et al, 2022). Additionally, it was found that Jorayal's farmers spend an average of NRs 11,223, which is NRs 43.01 less than Bogtan's farmers (NRs.…”
supporting
confidence: 86%
“…This information underscores the importance of understanding the dynamics of marketing channels and their impact on both producer income and overall market structure. Shrestha et al (2022), in their study in Tokha, Kathmandu, also found that as the number of intermediaries in the supply chain increases, the market margin increases while the producer's share decreases.…”
Section: Marketing Channelsmentioning
confidence: 91%